2020
DOI: 10.1182/bloodadvances.2020001443
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-β alleviates delayed tPA-induced adverse effects via modulation of MMP3/9 production in ischemic stroke

Abstract: Tissue plasminogen activator (tPA) is the only US Food and Drug Administration (FDA)–approved drug for ischemic stroke. However, delayed tPA administration is associated with increased risk of blood-brain barrier (BBB) disruption and hemorrhagic transformation (HT). Interferon-β (IFNβ), an FDA-approved drug for the treatment of multiple sclerosis, is a cytokine with immunomodulatory properties. Previous studies, including ours, demonstrated that IFNβ or type I IFN receptor signaling conferred protection agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“… 24 Now, thrombolytic therapy using tissue type plasminogen activator is regarded as the only globally approved treatment for ischemic stroke, but this therapy is limited by a short treatment window of time and low recanalization rates. 25 Thus, refraining from ischemic-reperfusion injury is critical for the treatment of patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Now, thrombolytic therapy using tissue type plasminogen activator is regarded as the only globally approved treatment for ischemic stroke, but this therapy is limited by a short treatment window of time and low recanalization rates. 25 Thus, refraining from ischemic-reperfusion injury is critical for the treatment of patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-b also plays an anti-inflammatory role in cerebrovascular diseases. IFN-b attenuates tight junction protein degradation in brain endothelial cells and affords protection against ischaemic stroke (Kuo et al, 2020). In intracranial hemorrhage, elevated levels of IFN-b and signal transducer and activator of transcription (STAT) 1 are accompanied by reduced levels of NLRP3 inflammasomes, caspase-1, and IL-1b (Wang, Nowrangi, et al, 2018).…”
Section: The Signal Pathway That Alleviates Cerebrovascular Diseasesmentioning
confidence: 99%
“…The studies employed mice, rats, or rabbits in various stroke models and the majority of these showed a positive effect regarding infarct volume [42][43][44] (additional source: poster of Veldhuis et al at the 2002 ISMRM-10th scientific meeting and exhibition in Honolulu, "Delayed treatment with interferon-beta protects against ischemic stroke", available online) and neurological function regain [44], while one did not show a protective effect and raised safety concerns for the substance [45]. Very recently, Kuo et al (2020) showed that IFN-b reduced the rates of mortality, of hemorrhagic transformation, and of adverse events induced by delayed rTPA administration, which has been associated with aggravated brain injury in a murine IS model [46].…”
Section: Dmds With Preclinical Evidence 321 Interferon Betamentioning
confidence: 99%